Physician and Nurse Perceptions of Gentle Cesarean Birth. Issue 2 (March 2018) - Mercier, Rebecca J.; Durante, Julia C.
Abstract: Background: Protocols for neonatal care and mother–baby interaction at cesarean birth frequently differ from those at vaginal birth. There is increasing interest in adopting family-friendly or gentle protocols for women having cesarean birth. Current evidence suggests challenges in achieving interdepartmental cooperation and consensus are potential barriers to implementing gentle cesarean protocols. Purpose: To describe how care providers' professional role and characteristics may affect perception about gentle cesarean birth techniques and inform specific concerns about protocol changes. Study Design and Methods: A cross-sectional survey with mixed-methods analysis incorporating quantitative and qualitative conventional content analysis was used. A structured survey was distributed via email to all care providers on the labor and birth unit, including attending physicians, resident physicians in training, fellows, labor nurses, respiratory therapists, and operating room technicians. Quantitative responses were analyzed with bivariable tests and logistic regression to describe associations between provider attitudes and provider characteristics. Open-ended responses were analyzed with conventional content analysis to develop a model describing influences on overall provider attitudes. Results: Physicians and nurses generally have positive attitudes on benefits of gentle cesarean techniques. Their perceptions overall are informed by the balance of concerns about patient safety and logistical challenges versus perceived benefits of the techniques. On an individual level, care provider demographic and professional characteristics of gender and prior experience affected attitudes more than their specific role in patient care. Clinical Implications: Most labor and birth care providers have positive attitudes about gentle cesarean birth. Implementation of such programs should prioritize patient safety, educate physician and nurses about potential benefits for patients, and use experienced physicians and nurses as ambassadors to increase acceptance. Abstract : Increasingly, women are requesting a more family-friendly cesarean birth, sometimes referred to as a gentle cesarean. As cesarean birth requires care from an interdisciplinary team, knowledge of their perceptions of pros and cons, and willingness to participate is useful to the maternity care leadership team before embarking on a program to promote gentle cesarean birth. In this study, care providers who participate in cesarean birth were surveyed about gentle cesareans. Findings can be used by other maternity care teams considering this approach.